Rare association of papillary carcinoma of thyroid with adult T-cell lymphoma/leukemia - Khadilkar Urmila; Mathai Alka; Chakrapani M; Prasad Krishna (Wolters Kluwer Medknow Publications, 2010)
Papillary carcinoma is the most common malignant tumor of the thyroid, especially in countries with adequate or excess iodine in diet. Many studies indicate that a sizable number of papillary cancer cases occur in a setting of chronic thyroiditis. But the tumor that arises more frequently in thyroiditis is malignant lymphoma. We report a rare association of papillary carcinoma of thyroid in an elderly lady with adult T-cell lymphoma/leukemia. Fine needle aspiration of the thyroid, neck nodes and evaluation of the bone marrow and peripheral blood helped in the diagnosis of papillary cancer coexisting with adult T-cell lymphoma/leukemia.